1999
DOI: 10.1103/physreve.60.2171
|View full text |Cite
|
Sign up to set email alerts
|

Electrical recordings from rat cardiac muscle cells using field-effect transistors

Abstract: Extracellular electrophysiological recordings were made from cardiac cells cultured for up to seven days over microfabricated arrays of field-effect transistors. The recorded signals can be separated mainly into two types of cell transistor couplings: one that can be explained entirely by purely passive circuitry elements, and a second where voltage-gated ion channels contribute greatly to the measured extracellular signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 19 publications
5
52
0
Order By: Relevance
“…18 Previous studies have discussed several different signal shapes of extracellular recordings in detail. 10,11 These studies found that peaks like ͑1͒ and ͑2͒ were present in all cases while differences were observed for the latter, slower components ͑3͒ and ͑4͒, as in our study. Sprössler et al 11 The numbering is used in accordance to Fig.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…18 Previous studies have discussed several different signal shapes of extracellular recordings in detail. 10,11 These studies found that peaks like ͑1͒ and ͑2͒ were present in all cases while differences were observed for the latter, slower components ͑3͒ and ͑4͒, as in our study. Sprössler et al 11 The numbering is used in accordance to Fig.…”
supporting
confidence: 53%
“…8 This cell type is well suited for our studies in two respects: ͑i͒ the cell line is robust and well understood, which allows convenient studies of the fundamental physics of the coupling and ͑ii͒ it is closely related to cardiomyocytes which have been used for in vitro pharmacological studies. 9,10 We compare our signals with ones from planar field-effect transistors ͑FETs͒ 10,11 and associate them with the point-contact model 12 in order to explain their shape physiologically. This analysis is important to understand how to associate the recorded signals to the cellular mechanisms generating them.…”
mentioning
confidence: 99%
“…It exhibits spontaneous contraction and firing of action potentials in cell culture. Thus it is a well suited model system to study bioelectronic devices [33,34]. We demonstrate the validity of our model and we show evidence for an improved seal resistance of HL-1 cells on nanocavity sensors compared to planar cell-chip interfaces.…”
Section: Introductionmentioning
confidence: 70%
“…Inhomogeneities of the membrane attached to a sensor are a prerequisite for the recording of cellular activity [29]. Inhomogeneities of cardiac cells on sensors are discussed elsewhere in detail [33,34]. A scaled conductance of the ion channels in the attached membrane by a factor χ i where i = Na, K, Ca…”
Section: A Propagation Of Action Potentialsmentioning
confidence: 99%
“…The time courses of all FET signals were the same for both types of FET ͑n = 14 cells͒. They resemble a combination of different signal components, which were already previously described: 11 ͑i͒ capacitive transients at the onset and offset of the voltage stimulus, caused by capacitive coupling of the stimulus through the attached membrane, [17][18][19] ͑ii͒ an increase of V FET to a steady-state amplitude, ͑iii͒ a partially instantaneous decline of V FET at the end of the stimulus ͑Ohmic coupling͒, and ͑iv͒ a slower relaxation of V FET , that is not observed for I M ͑electrochemical coupling͒. In all recorded signals, the amplitude for n-and p-FETs differed from each other, whereas the time course was always the same for both transistor signals.…”
mentioning
confidence: 86%